Management of hangman’s fracture with percutaneous transpedicular screw fixation - Wu, Yao-Sen (Springer-Verlag, 2012)
PURPOSE: This study describes a percutaneous technique for C2 transpedicular screw fixation and evaluates its safety and efficacy in the treatment of patients with hangman’s fracture. METHODS: Ten patients with hangman’s fracture were treated by percutaneous C2 transpedicular screw fixation. There are six males and four females, who were, based on the classification of Levine and Edwards, sorted as follows: type I fracture, three cases; type II, five cases; type IIa, two cases. The causes of injury were road traffic accident in six patients and falling injury in four patients. Other associated lesions included rib fractures (7 patients), head injuries (4 patients), and fractures of extremities (6 patients). RESULTS: The new technique was performed successfully in all cases. The average operation time was 98 min (range 60–130 min) and the estimated blood loss was 25 ml (range 15–40 ml). No complications such as vascular or neural structures injuries were found intraoperatively. Postoperative CT scans demonstrated that 17 (85 %) of 20 screws were placed satisfactorily, and 3 (15 %) screws showed perforations of the pedicle wall (<2 mm). These patients were asymptomatic and no further intervention was required postoperatively. After 8–25 months follow-up (mean 15.3 months), solid fusion was demonstrated by computed tomography. All cases got well-sagittal alignment and no angulation or dislocation was found at the segment of C2–C3. There was no loss of fixation. Clinical examination showed a full range of motion in the neck in all patients. CONCLUSIONS: The fluoroscopically assisted percutaneous C2 transpedicular screw fixation method is a technically feasible and minimally invasive technique for hangman’s fracture.